Sistem Kerja Bagian Pengelolaan Arsip Dinas Perpustakaan Kabupaten Batu Bara - Aura Adinda Puspita (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This research aims to examine and analyze the work system implemented by the archives management section at the Batu Bara Regency Library Service. Archives are an important source of information to support the smooth running of administration and public services, so their management requires an efficient and organized system. This research uses a qualitative descriptive approach, with data collection through interviews, observation and documentation studies. The research results show that the archive management work system at the Batu Bara Regency Library Service still faces several obstacles, such as limited facilities and infrastructure, as well as a lack of human resources trained in the field of archive management. However, the archives management department attempts to overcome this problem by implementing a system that is in accordance with existing procedures. It is hoped that the results of this research can provide recommendations for improving the records management work system in related agencies, in order to increase efficiency and effectiveness in public services.